2021
DOI: 10.1021/acsami.1c00554
|View full text |Cite
|
Sign up to set email alerts
|

Electron Donor–Acceptor Effect-Induced Organic/Inorganic Nanohybrids with Low Energy Gap for Highly Efficient Photothermal Therapy

Abstract: For the design and optimization of near-infrared photothermal nanohybrids, tailoring the energy gap of nanohybrids plays a crucial role in attaining a satisfactory photothermal therapeutic efficacy for cancer and remains a challenge. Herein, we report an electron donor−acceptor effect-induced organic/ inorganic nanohybrid with a low energy gap (denoted as ICG/Ag/ LDH) by the in situ deposition of Ag nanoparticles onto the CoAl−LDH surface, followed by the coupling of ICG. A combination study verifies that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…To improve the availability and relieve the side effects, a facile self-assembly method via the interaction between the hydrophobic molecules and amphipathic molecules is developed in this study. ICG, an amphipathic fluorescent dye, has been proved to be one kind of typical agent for PTT due to its desirable absorption at the near-infrared (NIR) [ 39 , 40 ], which has been approved by the FDA. However, free ICG has critical issues such as rapid elimination because of its small molecular size.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the availability and relieve the side effects, a facile self-assembly method via the interaction between the hydrophobic molecules and amphipathic molecules is developed in this study. ICG, an amphipathic fluorescent dye, has been proved to be one kind of typical agent for PTT due to its desirable absorption at the near-infrared (NIR) [ 39 , 40 ], which has been approved by the FDA. However, free ICG has critical issues such as rapid elimination because of its small molecular size.…”
Section: Resultsmentioning
confidence: 99%
“…For this objective, the injectable CDN hydrogel composed of a benzaldehyde-capped poly­(ethyl glycol) cross-linked carboxymethyl chitosan network (denoted as CMC/OHC-PEG-CHO) and a 3-aminophenylboronic acid cross-linked poly­(vinyl alcohol) network (PVA/3-AB) was synthesized through dynamic covalent bonding of benzoic-imine and borate ester, while LDHs were conjugated in the dynamic hydrogel via physical interaction like hydrogen bonding (Scheme ). Besides, it was found that indocyanine green (ICG) could be absorbed by LDHs, and doxorubicin hydrochloride (DOX) could be embedded into the hydrogel matrix. In this work, we demonstrated the functionalization of the injectable CDN hydrogel with embedded ICG and DOX for introducing the ability of photothermal therapy (PTT) and photothermal-triggered drug release. We have illustrated that the injectable CDN hydrogel is capable of embolizing the renal artery and can efficiently inhibit the subcutaneous tumor growth through the combination of PTT and chemotherapy on animal models.…”
Section: Introductionmentioning
confidence: 99%